Pomegranate Peel Powder: An Effective and Environmentally Friendly Tool for Developing Latent Fingerprints on Nonporous Surfaces - R. S. Darshan; Vaibhav Sharma; Anuj Sharma; Abhishek R. Rai; Poonam Kumari; Archana Gautam; Anubhav Singh; Vaibhav Mishra; Kumud Kant Awasthi; Mahipal Singh Sankhla (Journal of Forensic Science and Medicine)
Background: Invaluable forensic evidence can be found in latent fingerprints, which are invisible to the naked eye. The integrity of the evidence may be compromised by conventional fingerprint production techniques that use chemicals, powders, and lasers and pose environmental dangers. Pomegranate peel powder, made from the rind of the fruit that is native to the Middle East and South Asia, offers a natural alternative. Aims and Objectives: The usefulness of pomegranate peel powder as a non-damaging agent for latent fingerprint development on a variety of non-porous surfaces is investigated in this study. Materials and Methods: The powder is used to develop all three types of fingerprints i.e. sebaceous, eccrine and natural on various non-porous surfaces (steel, glass slide, iron and granite). Results: According to our study, pomegranate peel powder produces remarkable outcomes and highlights its non-toxic properties and ability to preserve the evidence. Conclusion: Pomegranate peel powder can be an effective and environmentally friendly alternative to traditional techniques for fingerprinting in forensic science.